Highly Stable Phosphonate‐Based MOFs with Engineered Bandgaps for Efficient Photocatalytic Hydrogen Production - Zhu, Yun‐Pei; Yin, Jun; Abou‐Hamad, Edy; Liu, Xiaokang; Chen, Wei; Yao, Tao; Mohammed, Omar F.; Alshareef, Husam N. (Advanced materials (Weinheim), 2020)
Photoactive metal–organic frameworks (MOFs) represent one of the most promising materials for photocatalytic hydrogen production, but phosphonate‐based MOFs have remained largely underdeveloped compared to other conventional MOFs. Herein, a photocatalyst of 1D titanium phosphonate MOF is designed through an easy and scalable stirring hydrothermal method. Homogeneous incorporation of organophosphonic linkers can narrow the bandgap, which is due to the strong electron‐donating ability of the OH functional group that can efficiently shift the top of the valence band, moving the light absorption to the visible portion of the spectrum. In addition, the unique 1D nanowire topology enhances the photoinduced charge carrier transport and separation. Accordingly, the titanium phosphonate nanowires deliver remarkably enhanced photocatalytic hydrogen evolution activity under irradiation of both visible light and a full‐spectrum simulator. Such concepts of engineering both nanostructures and electronic states herald a new paradigm for designing MOF‐based photocatalysts. Phosphonate metal–organic frameworks (MOFs) with tunable gaps are presented. Taking advantage of the controllable compositions and functionalities of MOFs, a titanium‐phosphonate‐based MOF for highly stable photocatalytic hydrogen evolution is showcased. The electron‐donating effect of the functional groups in the phosphonic ligands significantly modifies the electronic structure, thus promoting the photocatalytic activity.